(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
Corn (Zea mays L.) is one of the most cultivated crops in the world. In Brazil, this cereal has a wide diversity of use. Most of the areas where maize production is used is irrigation, however, when performed inadequately it becomes preponderant for salinization of soils. The effect of proline foliar application on the growth and physiology of the green maize cultivated in salinized soil was evaluated. The experiment was conducted at the Center for Agro-Food Science and Technology (CCTA), belonging to the Federal University of Campina Grande (UFCG), Pombal, PB, from March to April 2015, using maize variety AG 1051. The treatments consisted of two levels of soil salinity (EC = 3.26 and 0.86 dS/m) and five concentrations of proline (0, 2.5, 5.0, 7.5 and 10 mmol L -¹) applied by leaf on corn plants. The experimental design was completely randomized, in the 2 x 5 factorial scheme, with four replications. A higher growth and mass accumulation was observed when the plants were conducted in soil of lower salinity (CE = 0.86 dS/m). Transpiration was influenced by salinity and proline concentration. The highest rate of intercellular CO2 concentration (Ci) was obtained at the concentration of 7.5 mmol L-¹ proline. Proline concentrations did not influence the growth and mass accumulation aspects of maize.